Women Have Lower Mortality Than Men After Attending a Long-Term Medically Supervised Exercise Program. Issue 2 (March 2022) - de Souza e Silva, Christina Grüne; Nishijuka, Fabio Akio; de Castro, Claudia Lucia Barros; Franca, João Felipe; Myers, Jonathan; Laukkanen, Jari Antero; de Araújo, Claudio Gil Soares
Abstract : Purpose: Medically supervised exercise programs (MSEPs) are equally recommended for men and women with cardiovascular disease (CVD). Aware of the lower CVD mortality in women, we hypothesized that among patients attending a MSEP, women would also have better survival. Methods: Data from men and women, who were enrolled in a MSEP between 1994 and 2018, were retrospectively analyzed. Sessions included aerobic, resistance, flexibility and balance exercises, and cardiopulmonary exercise test was performed. Date and underlying cause of death were obtained. Kaplan-Meier methods and Cox proportional hazards regression were used for survival analysis. Results: A total of 2236 participants (66% men, age range 33-85 yr) attended a median of 52 (18, 172) exercise sessions, and 23% died during 11 (6, 16) yr of follow-up. In both sexes, CVD was the leading cause of death (39%). Overall, women had a more favorable clinical profile and a longer survival compared to men (HR = 0.71: 95% CI, 0.58-0.85; P < .01). When considering those with coronary artery disease and similar clinical profile, although women had a lower percentage of sex- and age-predicted maximal oxygen uptake at baseline than men (58 vs 78%; P < .01), after adjusting for age, women still had a better long-term survival (HR = 0.68: 95% CI, 0.49-0.93; P = .02). Conclusion: Survival after attendance to a long-term MSEP was better among women, despite lower baseline cardiorespiratory fitness. Future studies should address whether men and women would similarly benefit when participating in an MSEP. Abstract : We speculated that women would have better survival than men after attending a long-term medically supervised exercise program. After assessing 2236 participants (33% women) during a median follow-up of 11 yr, women had better survival (HR = 0.68: 95% CI, 0.49-0.93) than men, even with lower sex-adjusted cardiorespiratory fitness at baseline.